Acoustic Change Responses to Amplitude Modulation in Cochlear Implant Users: Relationships to Speech Perception - Han, Ji-Hye; Dimitrijevic, Andrew (Frontiers in Neuroscience, 2020)
Objectives The ability to understand speech is highly variable in people with cochlear implants (CIs) and to date, there are no objective measures that identify the root of this discrepancy. However, behavioral measures of temporal processing such as the temporal modulation transfer function (TMTF) has previously found to be related to vowel and consonant identification in CI users. The acoustic change complex (ACC) is a cortical auditory-evoked potential response that can be elicited by a “change” in an ongoing stimulus. In this study, the ACC elicited by amplitude modulation (AM) change was related to measures of speech perception as well as the amplitude detection threshold in CI users. Methods Ten CI users (mean age: 50 years old) participated in this study. All subjects participated in behavioral tests that included both speech and amplitude modulation detection to obtain a TMTF. CI users were categorized as “good” (n = 6) or “poor” (n = 4) based on their speech-in noise score (<50%). 64-channel electroencephalographic recordings were conducted while CI users passively listened to AM change sounds that were presented in a free field setting. The AM change stimulus was white noise with four different AM rates (4, 40, 100, and 300 Hz). Results Behavioral results show that AM detection thresholds in CI users were higher compared to the normal-hearing (NH) group for all AM rates. The electrophysiological data suggest that N1 responses were significantly decreased in amplitude and their latencies were increased in CI users compared to NH controls. In addition, the N1 latencies for the poor CI performers were delayed compared to the good CI performers. The N1 latency for 40 Hz AM was correlated with various speech perception measures. Conclusion Our data suggest that the ACC to AM change provides an objective index of speech perception abilities that can be used to explain some of the variation in speech perception observed among CI users.